Treatment of Large Knee Osteochondral Lesions With a Biomimetic Scaffold: Results of a Multicenter Study of 49 Patients at 2-Year Follow-up. (July 2014) - Berruto, Massimo; Delcogliano, Marco; de Caro, Francesca; Carimati, Giulia; Uboldi, Francesco; Ferrua, Paolo; Ziveri, Giovanni; De Biase, Carlo Felice
Background: Osteochondral knee lesions represent a challenging condition encountered by orthopaedic surgeons. A variety of methods have been developed to repair articular cartilage defects. However, these techniques are limited by donor site morbidity or by the requirement for a staged procedure. Purpose: To assess the effectiveness of a biomimetic osteochondral scaffold for the treatment of large osteochondral knee lesions. Study Design: Case series; Level of evidence, 4. Methods: From 2009 to 2011, a total of 49 patients affected by isolated large osteochondral knee lesions (mean [± SD] size, 4.35 ± 1.26 cm 2 ) were treated with the biomimetic scaffold. Patients were evaluated using the International Knee Documentation Committee (IKDC), Tegner, and visual analog scale (VAS) pain scores, as well as magnetic resonance imaging (MRI) up to 3-year follow-up. The MOCART (magnetic resonance observation of cartilage repair tissue) score was performed to analyze different variables. Biopsies were carried out in 5 patients. Four of the 5 second-look arthroscopies and biopsies were performed on patients with failed results because of ethical issues. Results: The mean IKDC subjective score increased significantly from 45.45 ± 19.29 preoperatively to 70.86 ± 18.08 at 1-year follow-up and to 75.42 ± 19.31 at 2-year follow-up ( P < .001). The IKDC objective score changed from 50% normal and nearly normal knees before treatment to 89.79% at the 2-year follow-up. There was a statistically significant improvement ( P < .005) in VAS score from the preoperative level (6.69 ± 1.88) to the 2-year follow-up (1.96 ± 2.47). Tegner scores increased ( P < .001) from the preoperative value (2.20 ± 0.67) to the 2-year follow-up (4.9 ± 1.73) without achieving preinjury level. A correlation was found between the IKDC subjective score and age ( P < .001, r = −0.497, ρ = −0.502). Patients affected by osteochondritis dissecans (OCD) achieved a statistically significantly better outcome ( P < .05). A subgroup of 19 competitive athletes showed a statistically significantly improvement ( P < .001) in the subjective IKDC (86.5 ± 13.2) compared with the nonathletic subpopulation (69.03 ± 19.41) at the 2-year follow-up. The MRI findings of 30 patients were available at 2-year follow-up: 70% showed complete filling of the lesion, 63.3% had an intact articular surface, and 86% had mild or no effusion. In all cases, in dual T2-weighted fast spin echo sequence, the repair tissue showed a hyperintensive signal with respect to the surrounding subchondral bone; however, no edema was observed. Conclusion: The study findings indicate that the biomimetic scaffold that was investigated is an off-the-shelf, cell-free, and cost-effective implant that can regenerate either cartilage or subchondral bone. The scaffold allows a 1-step surgical procedure that can be used for osteochondral lesions, OCD, and in some cases osteonecrosis.